Rag and bone ebook - Benn, James R. (Billy Boyle World War II Mystery, 2010)
The fifth Billy Boyle investigation American Lieutenant Billy Boyle is assigned to London by his uncle, General Dwight D. Eisenhower, to investigate the murder of a Russian security officer in the buildup to D-Day. Billy recognizes that this is a politically charged case, pitting Allies against one another, and that he must proceed with caution. The Polish contingent is incensed over evidence that implicates the Russians in the murder of hundreds of Polish prisoners in the so-called Katyn Forest Massacre, and Scotland Yard thinks this murder of a Soviet officer may be a revenge killing—perhaps perpetrated by Billy’s friend Kaz, a Polish baron in exile. But Billy doesn’t buy it. Can he find the real murderer, exonerate his friend, and prevent Allied relations from falling to pieces at this critical moment of the war?